Integration model of halal principle, lean six sigma, and sustainability for better operational performance at poultry industry in Indonesia - Muhammad Faishal (2024)
The operational performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia’s poultry industry is critical, given the industry's substantial contribution to the national economy. Despite significant annual investments aimed at stimulating related economic activities, the sector continues to face challenges such as adherence to Halal Principles (HP), inefficient processes, quality issues, limited product innovation, and negative environmental and social impacts, which hinder sustainable economic growth. Consequently, many MSMEs within this sector have struggled, with some ceasing operations. Therefore, this study aims to explore the impact of Halal Principles on the operational performance of MSMEs in the poultry industry, with Lean Six Sigma (LSS) and Sustainability (S) considered as mediating factors. A survey research design incorporated a quantitative method and cross-sectional study of MSMEs poultry industries' owners or head managers to test the hypothesized relationship among various constructs. The sampling frame of the target population was not available. Hence, this study had to develop a sampling frame and distribute structured questionnaires face-to-face to collect quantitative data. From the total collected questionnaires, 249 responses were selected through random sampling. Data were analyzed using Structural Equation Modelling (SEM) technique through IBM-SPSS-AMOS version 24.0 software. The results revealed that Halal Principles significantly influence to Operational Performance but not supported to Sustainability. LSS not only has a direct positive effect on Operational Performance but also partially mediates the relationship between Halal Principles and Operational Performance. Similarly, Sustainability significantly enhances Operational Performance and partially mediates the impact of Halal Principles and LSS on Operational Performance. The novelty of the research was constructing an inductive model called the Halal LSS Model (HLSSM), which theoretically implied relationships among LSS, Halal Principle, Sustainability, And Operational Performance. The research introduces a novel theoretical framework is HLSSM, which integrates Halal Principles, LSS, and Sustainability to provide a comprehensive understanding of their combination effects on Operational Performance. The other influencers were Sustainability and LSS, which partially mediate the relationship between Halal Principle and Operational Performance. This model offers valuable insights for practitioners and policymakers, suggesting that a strategic focus on these interconnected elements can lead to substantial improvements in the operational performance of MSMEs in the poultry industry. The research outcomes are particularly relevant for industry leaders and government agencies aiming to spur sustainable economic development within this vital sector.